A novel and efficient synthesis of reduced TiO2/C nanocomposites with mesopores for improved visible light photocatalytic performance. (7th June 2017) - Sha, Dawei; Wang, Jingjing; Ye, Nanfei; Dai, Yu; Ren, Jie; Chen, Ming; Wu, Yanze; Wang, Qiong; Tang, Hua; Yan, Xuehua
Abstract: There are some problems in TiO2, such as poor visible light response, low surface area and high electro-hole combination efficiency, which limit its applications. A novel and efficient solvothermal method was developed using TiCl3 and glucose to prepare reduced TiO2 /C (r-TiO2 /C) nanocomposites. The results show that TiO2 in composite is anatase and reduced. Transmission electron microscope analysis indicates that the composites are composed of r-TiO2 and amorphous carbon in size of 8–14 nm. All samples have a good response in visible light and near infrared region. When 1.5 mmol glucose was used, the sample has the lowest band gap 1.30 eV according to Ultraviolet–visible spectroscopy, the degradation ratio of which for Rhodamine B reaches 92% after 70 min under visible light irradiation.